Diseases of the spinal cord : novel imaging, diagnosis and treatment - Hattingen, Elke; Weidauer, Stefan; Setzer, Matthias; Klein, Johannes C.; Vrionis, Frank (Springer Berlin Heidelberg Imprint: Springer, 2015)
Spinal cord imaging has significantly benefited from new MR imaging methods such as cardiac-gated diffusion-weighted imaging, diffusion tensor imaging with fiber tracking, and time-resolved MR angiography. Recent decades have also witnessed fundamental progress in understanding of the pathophysiology of vascular, metabolic, and inflammatory spinal cord diseases. Furthermore, neurosurgical procedures and endovascular treatments of spinal cord diseases have been improved and perfected to avoid severe neurological sequelae.   This textbook provides an interdisciplinary overview of the new imaging modalities, identifies clues for MR imaging diagnosis and differential diagnosis, and describes the anatomical background required to understand spinal cord diseases. Important neurological symptoms are highlighted, and modern treatment options for different diseases are fully explained and discussed. High-quality illustrations, including numerous images, are provided for all important spinal cord diseases, documenting relevant anatomical details, special MR imaging methods, differential diagnoses, and possible treatment procedures.